An Analysis Of Students’ Difficulties In Speaking English Through Conversation - Nurcahaya Citra Resmi Gulo; Feby Meuthia Yusuf; Yessy Marzona (Kilau Publishing, 2026)
This study aims to analyze students' difficulties in speaking English through conversation at Ekasakti High School, Padang. Speaking is a very important language skill in supporting communication; however, many students still experience difficulties in expressing ideas orally in English. This study used a descriptive research design. The study population was all nine grade XI IPS students at Ekasakti High School, Padang, and all of them were used as a sample (total sampling). The research instrument was a speaking test in the form of an English conversation on the topic